The Carbothalamus: Villain and Victim in Metabolic Care - Parag Agrawal; Khushboo Agarwal; Nitin Kapoor; Sanjay Kalra (Journal of the Pakistan Medical Association, 2026)
The hypothalamus, through its expression and interaction with various neurotransmitters, pituitary hormones and orexigenic and anorexigenic signals, regulates appetite. Leptin and insulin, released in response to food intake, act as anorexigenic stimuli whereas ghrelin, released in fasting, is orexigenic. Imbalance in these signals can lead to disorders in appetite regulation with cardiovascular implications. Glucose, through multiple mechanisms, shows an addictive potential and interacts and affects the hypothalamic regulation of appetite and energy metabolism. The concept of Carbothalamus integrates the hypothalamic function in response to carbohydrate craving and proves opportune to identify the individual maladaptation and an approach to manage the same. This simple concept helps understand, as well as address, obesity in an easy and effective manner. Keywords: Carbohydrates, hypothalamus, incretins, nutrition, obesity, overweight, weight